1993
DOI: 10.2527/1993.7171853x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of animal protein supplements in diets of early-weaned pigs2

Abstract: Three growth assays were conducted to determine the efficacy of replacing dried skim milk and(or) dried whey in diets of starting pigs with commercially available spray-dried porcine plasma, spray-dried porcine blood, spray-dried bovine plasma, or spray-dried extracted meat protein. In Exp. 1, 236, 24-d-old crossbred pigs were fed diets containing either skim milk and whey or porcine plasma from 0 to 14 d postweaning and whey or porcine plasma from 14 to 28 d. Although pigs fed diets containing porcine plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
2
30

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 12 publications
8
63
2
30
Order By: Relevance
“…Neither daily feed intake nor feed conversion was affected by the experimental diets during this period (P>0.05). In contrast, Hansen et al (1993) and Kats et al (1994) observed higher daily feed intake by piglets consuming complex diets when compared with animals receiving the control diet. Means followed by the same letter within the row are similar by the SNK test (5 %).…”
Section: Resultsmentioning
confidence: 87%
“…Neither daily feed intake nor feed conversion was affected by the experimental diets during this period (P>0.05). In contrast, Hansen et al (1993) and Kats et al (1994) observed higher daily feed intake by piglets consuming complex diets when compared with animals receiving the control diet. Means followed by the same letter within the row are similar by the SNK test (5 %).…”
Section: Resultsmentioning
confidence: 87%
“…Efeitos positivos da adição de plasma sobre o GPMD dos leitões pós-desmame também foram verificados por Hansen et al (1993), que relacionaram essa melhora ao maior consumo de ração.…”
Section: Resultsunclassified
“…O plasma sangüíneo em pó pode ser uma fonte efetiva de proteína animal, por aumentar o consumo de ração e o ganho de peso pós-desmame (Ermer et al, 1992;Hansen et al, 1993;Touchette et al, 2002;Lawrence et al, 2004), diminuir a incidência de diarréia pós-desmame (Russel et al, 1996;Harrell et al, 2000;Owusu-Asiedu et al, 2002) e possuir efeito protetor ao intestino delgado (Torrallardona et al, 2003).…”
Section: Introductionunclassified
“…Animal plasma (AP) is a potent source of immunoglobulins (Igs) and, when included in the diets of healthy weaned production animals, has been shown to improve voluntary feed intake, growth rate and intestinal growth (Hansen et al, 1993;Kats et al, 1994). This effect may be due to a greater availability of nutrients and energy for growth, consequent upon a lower degree of immune cell activation (Demas et al, 1997).…”
Section: Introductionmentioning
confidence: 99%